MANAJEMEN PENINGKATAN PROFESIONLISME TENAGA PENDIDIK DI PERGURUAN TINGGI - Adi Musharianto; Mochammad Yana Aditya (Manajemen Pendidikan, 2022)
The presence of lecturers is closely related to the teaching and learning process on campus, which affects the quality of graduates. Therefore, qualified lecturers are needed, namely lecturers who can carry out responsibilities in the teaching and learning process. The quality of teachers or lecturers can be reflected in their level of professionalism, namely expertise in carrying out work carried out effectively and efficiently. This study aims to analyze the professionalism of lecturers in providing learning materials to students on student assessments based on the dimensions of reliability, responsiveness, assurance, and empathy. The method and approach in this research is descriptive analytic by using primary data through questionnaires. From the results of the study, it can be concluded that exogenous variables in professionalism along with their indicators have proven to be strong in shaping the professionalism of lecturers so as to increase student satisfaction. This study uses limited variables and indicators. The weakness of this research can be supported by other, more comprehensive research.